β3GnT8 Promotes Colorectal Cancer Cells Invasion via CD147/MMP2/Galectin3 Axis - Jiang, Zhi; Zhang, Huan; Liu, Chunliang; Yin, Jun; Tong, Shan; Lv, Junxing; Wei, Shaohua; Wu, Shiliang (Frontiers in Physiology, 2018)
β1,3-N-acetylglucosaminyltransferase (β3GnT8) and β3GnT2 are key enzymes that catalyzes the formation of polylactosamine glycan structures by transferring GlcNAc to tetra-antennary β1-6-branched N-glycan and it also has an important effect on the progression of various types of human cancer. They have been reported to participate in tumor invasion and metastasis by regulating the expression of matrix metalloproteinases (MMPs), CD147, and polylactosamine. However, whether β3GnT8 and β3GnT2 play a role in colorectal cancer and, if so, the underlying mechanisms remain unclear. In our study, we detected the expression of β3GnT8, CD147, MMP2, and galectin3 by immunohistochemistry on 90 paraffin-embedded slices. And β3GnT8, CD147, MMP2, and galectin3 were over-expressed in colorectal cancer tissues. We found that overexpression of β3GnT8 and β3GnT2 promoted invasion of colorectal cancer cells, whereas knockdown of β3GnT8 and β3GnT2 inhibited the invasive activity. Mechanistically, β3GnT8 and β3GnT2 regulated the expression of HG-CD147 and the level of polylactosamines in colorectal cancer cells. Together, these results illustrate that the novel role and the molecular mechanism of β3GnT8 and β3GnT2 in promotion of colorectal cancer invasion. These results suggest that the potential use of β3GnT8 as a tumor target for the therapy of colorectal cancer.